Camptothecin Delivery via Tumor-Derived Exosome for Radiosensitization by Cell Cycle Regulation on Patient-Derived Xenograft Mice - Yang, Yiling; Ren, Shiqi; Huang, Wenpeng; Dong, Jiahan; Guo, Jiancheng; Zhao, Jie; Zhang, Yonggao (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract Purpose: While radiotherapy remains the leading clinical treatment for many tumors, its efficacy can be significantly hampered by the insensitivity of cells in the S phase of the cell cycle to such irradiation. Methods: Here, we designed a highly targeted drug delivery platform in which exosomes were loaded with the FDA-approved anti-tumor drug camptothecin (CPT) which is capable of regulating cell cycle. The utilized exosomes were isolated from patient tumors, enabling the personalized treatment of individuals to ensure better therapeutic outcomes. Results: This exosome-mediated delivery strategy was exhibited robust targeted to patient-derived tumor cells in vitro and in established patient-derived xenograft models. By delivering CPT to tumor cells, this nanoplatform was able to decrease cell cycle arrest in the S phase, increasing the frequency of cells in the G1 and G2/M phases such that they were more radiosensitive. Conclusion: This therapeutic approach was able to substantially enhance the sensitivity of patient-derived tumors to ionizing radiation, thereby improving the overall efficacy of radiotherapy without the need for a higher radiation dose.